Responses and Expectations Regarding Municipality Declaration: A Case of Baglung Municipality - Bajracharya, Kishor Bajra (The Third Pole: Journal of Geography Education, 2014)
The process of declaration of municipality is taking place in Nepal at times but not in the regular way and with given regulations. Transformation into a municipality has been regarded as a matter of great pride and reputation in many cases, so was the case of Baglung as well. The proclamation of municipality does not possess any probation period to make any necessary modification. When the people have to face taxation and many other economic liabilities after having the designation of municipality, a sort of uneasiness and inconvenience grips them. Nothing was known in this regard in many cases and Baglung is not an exception. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11508 The Third Pole: Journal of Geography Vol.8-10, pp. 20-26: 2010